Literacy and Numeracy Development: A Comparative Study Between Indonesia and Australia - Nurul Awalliyah; Barokah Rahma; Ika Kurnia Sofiani (Penerbit Hellow Pustaka, 2025)
This study compares literacy and numeracy development policies and practices between Indonesia and Australia, focusing on national assessments, learning strategies, and teacher quality and professional development. In Australia, the National Assessment Program-Literacy and Numeracy (NAPLAN) is the main instrument in monitoring student achievement and promoting data-driven interventions. Indonesia, on the other hand, is implementing the National Assessment and Merdeka Curriculum in response to the challenges of 21st century education quality and relevance. Indonesia struggles with infrastructure inequality, teacher quality and policy implementation readiness, while Australia faces education disparities between urban and rural communities and indigenous groups. This research uses a desk study approach to analyze policy documents, scholarly publications and official reports from both countries. The results show that strengthening literacy and numeracy requires a systemic approach that includes flexible curriculum planning, informative assessments, ongoing teacher training and the use of data for continuous improvement. This cross-country study provides important insights for policymakers and education practitioners in designing contextualized and sustainable education quality improvement strategies, especially in strengthening students' essential competencies to face global challenges.